VIV suppression for a large mass-damping cylinder attached with helical strakes. (April 2016) - Sui, Juan; Wang, Jiasong; Liang, Shengping; Tian, Qilong
Abstract: The experiments on vortex-induced vibration (VIV) suppression for a circular cylinder with helical strake by varying its heights, pitches, coverages and cross sections were carried out in a wind tunnel at Reynolds number (Re) ranging from 2.7×10 3 to 5.79×10 4 . The bare cylinder with large mass-damping parameter ( m * ζ =1.415, where m * is the mass ratio and ζ is the structural damping factor) was flexibly mounted. The response characteristics were analyzed by comparing with the classical experimental results under different mass-damping parameters. Two-degree-of-freedom (2DOF, cross-flow (CF) and in-line (IL)) displacements of the cylinder with and without helical strakes were measured by two laser sensors. All amplitude responses of cylinders attached with helical strake of m * ζ varying from 1.966 to 3.354 are less than those of the bare cylinder. The strake height and coverage have a great influence on the VIV suppression rather than the strake pitch. The helical strake of P / D =5, h / D =0.14 ("D"-type) is the most effective one, with which the VIV suppression efficiency on the root-mean-square (RMS) value of CF amplitude reaches up to over 85% and the maximum suppression efficiency reaches up to 98% at U r =20 in the peak region. Flow visualizations of bare cylinder and straked cylinder of P / D =10, h / D =0.10 on the plane perpendicular to the cylinder axis were conducted in different conditions, and it can be found that helical strake can change vibration frequencies, and suppress the vortex shedding of circular cylinder by varying the separation points, avoiding the interaction between the two shear layers, reducing the vortex structures scale, resulting in vibration suppression of bare cylinder. Highlights: VIV suppression on large mass-damping cylinder was presented and verified. Experiments was carried out for strakes at different geometries and cross-sections. The RMS amplitudes of "D"-type are decreased up to 85% in the CF direction. The helical strake of P / D =0.14, h / D =5 has the best suppression efficiency. Helical strakes can alter vortex shedding of bare cylinder.